Public health audit of vaccine cold chain management in general practice and community pharmacy in Western Australia - Adeline Hillan; Li Pung; Susan Ridderhof; Jessica Ramsay; Rashmi Vinogradov; Darren Westphal; Mayli Foong; Alan Leeb; Benjamin Scalley; Anastasia Phillips (Elsevier, 2024)
Objective: To support immunisation providers through a cold chain management audit. Methods: An electronic audit survey using the National Vaccine Storage Guidelines as a gold standard was developed for general practice (GP) and community pharmacy. It included automated feedback, with individualised support from a clinical nurse specialist as required. Responses were analysed to determine the proportion of providers meeting criteria in four categories: procedures, refrigerators and equipment, temperature monitoring and emergency storage. Results: Of 818 providers invited, 420 GPs (89.6%) and 276 pharmacies (82%) responded. Over 70% met all procedural and emergency storage criteria. Although most providers (98.1% GPs, 97.0% pharmacies) used a data logger, the proportion measuring at 5-minute intervals, reviewing data logger printouts weekly and manually recording minimum and maximum temperatures was lower. In total, 58% of providers required follow-up by the clinical nurse specialist, most regarding the need for equipment. Conclusion: An electronic audit enabled public health to engage with a large number of immunisation providers. Most reported high compliance with the national guidelines although opportunities for education were identified and actioned. Implications for Public Health: Electronic solutions can support public health units to engage with providers to ensure vaccines remain effective and wastage is limited.